Research Methodology - Saliza Azlina Osman,; Nurulhidayah Basari,; Norhazirah Kemin, (2026)
This Research Methodology Module is designed to provide postgraduate students at UTHM with a structured and comprehensive approach to understanding and applying research methodologies in academic studies. It offers a detailed exploration of the principles. techniques, and ethical considerations that support scientific inquiry across diverse disciplinesThe module is carefully organized to guide postgraduate students through fundamental concepts of research, including hypothesis development, data collection, and analysis, with a balanced emphasis on qualitative and quantitative methods. It also features in-depth discussions on data analysis techniques and related aspects of research. Furthermore, the use of artificial intelligence (AI) in streamlining literature reviews is highlighted as a critical tool for postgraduate research endeavors.This module represents a collaborative effort by academics to ensure its relevance and alignment with postgraduate academic needs. It serves as an essential resource for postgraduate students, empowering them to strengthen their methodological capabilities and excel in their academic pursuits.